The Role of Narcism in The Detection of Financial Fraud: A Systematic Literature Review - Amalia, Dewi; Tarjo, Tarjo; Muhammad, Erfan; Said, Jamaliah (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2023)
Introduction / Main Objectives: This article aims to map the literature review regarding financial fraud detection by analyzing narcissistic individuals when using social media. Background Problems: The writer found indications of narcissism in the literature with the keywords